Managing logistics and transportation in the public sector - Matthews, Darin L.; Stanley, Linda L. (Routledge, 2023)
Managing Logistics and Transportation in the Public Sector, Second Edition thoroughly examines the world of transportation as it relates to public procurement, stressing the importance of not only procuring the right goods, materials, and services, but also ensuring the proper delivery of those goods, materials, and services to their final destination. Designed to educate the public procurement professional on ways to realize enhanced cost savings, an introduction to the history of transportation is offered, as well as industry terminology and accepted practices. Authors Darin Matthews and Linda Stanley explore recent transportation industry evolutions, including the development of important technologies like package tracing, delivery notification, and drone delivery, and ways to successfully integrate this technology. Sustainability in transportation, including product packaging, material reuse, and reduced emissions for delivery vehicles are likewise examined. Through the use of case studies, quiz questions, PowerPoint slides, industry websites, and recommended readings, Managing Logistics and Transportation in the Public Sector, Second Edition offers a complete package for professionals in public procurement looking to enhance their knowledge of logistics and transportation, as well as for university courses on transportation, supply chain management, and public procurement.